First Line Androgen Deprivation Therapy vs. Chemotherapy for Patients With Androgen Receptor Positive Recurrent or Metastatic Salivary Gland Carcinoma—A Retrospective Study - Viscuse, Paul V.; Price, Katharine A.; Garcia, Joaquin J.; Schembri-Wismayer, David J.; Chintakuntlawar, Ashish V. (Frontiers in Oncology, 2019)
Objectives: There is a lack of effective therapy for recurrent or metastatic salivary gland carcinoma. Androgen deprivation therapy has demonstrated efficacy in cases of salivary duct carcinoma and high-grade adenocarcinoma not otherwise specified that express androgen receptor. Materials and Methods: We conducted a single institution retrospective cohort study examining patients treated for recurrent/metastatic salivary duct carcinoma or high-grade adenocarcinoma not otherwise specified of the salivary gland. Survival analyses were performed to assess for efficacy of first-line androgen deprivation therapy versus first-line conventional cytotoxic chemotherapy. Efficacy of salvage androgen deprivation therapy was also assessed. Results: Fifty-eight patients were reviewed. Thirty-five patients had recurrent/metastatic disease of which 28 had salivary duct carcinoma (80%) and 7 had high-grade adenocarcinoma not otherwise specified (20%). Median overall survival for first-line androgen deprivation therapy was 25 months compared to 25 months for first-line chemotherapy [RR 0.54 (0.23-1.28, p=0.16)]. Patients treated with first-line androgen deprivation therapy had a response rate of 45% (9/20) and patients treated with first-line chemotherapy had a response rate of 14% (2/14). Six patients received salvage androgen deprivation therapy with 1 patient demonstrating complete response and 3 with stable disease as best response (clinical benefit rate 67%). Conclusion: Overall survival for first line androgen deprivation therapy and first line cytotoxic chemotherapy was comparable but response rates to first-line androgen deprivation therapy were higher than those with first-line chemotherapy. Salvage androgen deprivation therapy is active in recurrent/metastatic salivary gland carcinoma.